Field patterns of scientometric indicators use for presenting research portfolio for assessment. Issue 2 (30th January 2019) - Kulczycki, Emanuel
Abstract: This study investigates what names of metrics or databases researchers use to present their research portfolio and how their use is influenced by the field. I have analysed the data comprising 3, 695 self-presentation documents (82, 710 pages) from various academic promotion procedures in Poland. My study aims to determine the differences in the use of scientometrics indicators across all fields of science. I have used 21 codes (metrics and databases' names) for coding all documents, analysed the patterns of scientometric indicators use, and found out that there is a significant relation between publication patterns and patterns of scientometric indicators use. My analyses reveal that researchers in 'Hard Sciences' (except for mathematics) very often use metrics to describe their output, researchers in 'Soft Sciences' (except for economics) only occasionally use metrics, and scholars from 'Arts' hardly ever use metrics. My most noteworthy finding highlights that patterns of scientometric indicators use are related to the publication patterns in the given field. I conclude with several recommendations for various research policies and show what metrics could be used and expected in promotion procedures in various fields.